Persepsi Mahasiswa Prodi Agroindustri terhadap Praktikum dengan Video Demonstrasi pada Mata Kuliah Analisa Pangan - Ratnawati Hermanto, Sarwendah; Syawaldi, Syawaldi (Jurusan Teknik Sipil, Politeknik Negeri Ketapang, 2024)
The Covid-19 pandemic has made many changes, especially in the field of education. Learning, which was originally carried out face-to-face, is required to switch online for both theory and practicum courses. Students' perception of online lectures can help students improve their understanding and knowledge of the courses they take, in this case food analysis courses. This study aims to find out students' perception of practicum with demonstration videos in food analysis courses. This research is a qualitative descriptive research. The sample was taken using a simple random sampling technique totaling 50 students. Research data was obtained using questionnaires and in-depth interviews. Student perception can be seen from three aspects, namely the teaching and learning process, lecturers' abilities and facilities and infrastructure that are assessed using the Likert scale. The data analysis techniques used in this study are qualitative analysis, namely data collection, data reduction, data presentation, and conclusion drawn. Overall, student perception in all aspects has an average of 60.92% consisting of 59.6% of teaching and learning activities, 68.7% of lecturer competence and 54.4% of facilities and infrastructure, so that students' perception of practicum with video demonstrations in food analysis courses is positive